The BERA/SAGE handbook of educational research - Wyse, Dominic 1964-; Selwyn, Neil; Smith, Emma (Professor); Suter, Larry (Sage Reference, 2017)
The British Educational Research Association (BERA) has worked with SAGE to develop a high quality research methods handbook for students studying education and related areas. The book is published in two volumes and over 1,000 pages. The contributions are listed thematically in six parts, progressing from a background to research enquiry, through planning research, approaches or design, acquiring data, analysis and lastly reporting, disseminating and evaluation. Over 50 authors are included, many highly eminent in their fields. This handbook makes a valuable and authoritative contribution to the research endeavour for all those working or studying in the field of education. [Publisher website, ed].